Public health sustainability: Performance analysis of circular patch antenna for non-ionizing radiation (NIR) level measurement - Abdul Rahman S.N.D.; Sabri N.H.; Jaafar H.; Umar R.; Ghazali M.I.M.; Dagang A.N. (Universiti Malaysia Terengganu, 2024)
Indexed by SCOPUS/ERA